1) Simplify the expression fully. 2) If 3^-x =t =4t, express 4 ^x-1 +4^x+1 / 17.2 ^x, in terms of t
in Algebra 1 Answers by Level 1 User (680 points)

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Best answer

I read this as:

(1) 4ˣ⁻¹+4ˣ⁺¹)/(17×2ˣ)=

4ˣ⁻¹(1+4²)/(17×2ˣ)=

4ˣ⁻¹(17)/(17×2ˣ)=

4ˣ⁻¹/2ˣ=2²ˣ⁻²⁻ˣ=2ˣ⁻².

(2) There seems to be a typo in this part, because 4t=t implies t=0. 

If 3⁻ˣ=t, then log(3⁻ˣ)=log(t), -xlog(3)=log(t), x=-log(t)/log(3).

(4ˣ⁻¹+4ˣ⁺¹)/(17×2ˣ)=2ˣ⁻²=2^(-log(t)/log(3)-2)=

2^-((log(t)+log(9)/log(3))=2^-(log(9t)/log(3)).

If 3⁻ˣ=4t, (4ˣ⁻¹+4ˣ⁺¹)/(17×2ˣ)=2^-(log(36t)/log(3)).

by Top Rated User (880k points)
selected by
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
86,734 questions
93,245 answers
2,332 comments
24,131 users